What gives Bolt the edge—A.V. Hill knew it already! - Beneke, R.; Taylor, M. J. D. (Journal of Biomechanics, 2010)
The 100 m is the blue ribboned event of world athletics competitions, with the winner crowned as the fastest human on Earth. Currently that fastest human is Usain Bolt, who covers 100 m in 9.58 s, achieving an average velocity of 10.43 m s-1. Bolt is a phenomenal athlete, but what is his trick? Using Hills model, relating muscle force and heat liberation to shortening velocity, we propose that Bolt is at an advantage in relative power development and biomechanical efficiency compared to his contemporaries.